HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN STATUS GIZI IBU HAMIL DI PUSKESMAS WATAMPONE KABUPATEN BONE - Mustar (LPPM Institut Sains dan Kesehatan Bone, 2015)
Food consumption is one of the factors that has a direct effect on a person's nutritional status. Problems and conditions that often occur in pregnant women are not being aware of an increase in nutritional needs during pregnancy. The application of the relationship between knowledge and nutritional status that occurs in pregnant women is very important so that the baby is still healthy. This study aims to determine the level of knowledge of pregnant women in the working area of ​​the health center on the nutritional status of pregnant women and the relationship between knowledge of pregnant women and nutritional status in the work area of ​​Puskesmas Watampone. The method used in this research is a quantitative type, data obtained through observation, interviews and documentation, then analyzed bivariately using the chi square test. The results showed that the level of knowledge of pregnant women with a sufficient level of knowledge was 105 people (56.6%), and less knowledge was 55 people (34.4%). As for the relationship between knowledge of pregnant women with good nutritional status with adequate knowledge of 84 people (80%) and knowledge of pregnant women with sufficient knowledge of poor nutritional status as many as 21 people (20%), and knowledge of pregnant women with poor nutritional status as many as 19 people (49.1%), and knowledgeable Good nutrition and less knowledgeable as many as 36 people (50.9%). The C-square test results obtained p value = 0.00, which means that the p value is smaller than the alpha value (0.05). There is a significant relationship between pregnant women who are knowledgeable enough to knowledge about nutritional status